Latent tuberculosis infection in health-care workers in the government sector in Brunei Darussalam: A cross-sectional study - Nurin Jazmina Muhammad Syafiq; Ashishkumar Akshaykumar Trivedi; Alice Lai; Maria Pureza Aurelio Fontelera; Mei Ann Lim (Wolters Kluwer Medknow Publications, 2023)
Objective: Health-care workers (HCWs) are known to be at high risk for occupational biological hazards, and this includes exposure to mycobacterium tuberculosis (TB) which can result in either active or latent TB infection (LTBI). This study aims to provide an overview of the incidence of LTBI among HCWs in Brunei Darussalam, to examine associated risk factors, and to evaluate LTBI treatment compliance. Materials and Methods: This is a retrospective cross-sectional study which was conducted using data from January 2018 to December 2021, on notified cases of LTBI in HCWs which identified 115 cases. Demographic data, underlying medical conditions, and compliance to treatment were assessed through reviews of their electronic health records. Results: The incidence of LBTI was 14.6/year/1000 HCWs. The incidence rate reached a high of 24.6/1000 in 2020, and majority of cases were in the older age groups. There was good treatment acceptance and compliance (82.6%), and this was observed to be significantly higher in females than males (P = 0.02). Conclusion: This study showed an average incidence of LTBI of 14.6/1000 HCWs over 4 years and high LTBI treatment acceptance (82.6%) and compliance. Emphasis on infection prevention and control measures in health-care settings and actions to increase awareness of LTBI are crucial interventions toward reducing the burden of LTBI.